Melatonin inhibits ethylene biosynthesis by regulating MdERF1/MdERF3 pathway during apple fruit ripening - Chen Li; Qian Yu; Yanmin Du; Wenhui Wang; Yajing Si; Yuling Liang; Shijiao Lin; Guangxin Yang; Weiting Liu; Aide Wang; Yinglin Ji (Postharvest Biology and Technology, 2026)

Targeting the NLRP3/Caspase-1 pyroptotic pathway exacerbates insulin resistance upon exposure to nanoplastics with different surface chemistries - Xinxin Yao; Yu Cao; Sue Lin; Shihua Chen; Feiqin Xie; Wenhui Xu; Yize Wu; Qiufang Wu; Renyi Peng; Xiaohua Gong (Journal of Hazardous Materials, 2026)

Nitrogen input drives niche partitioning and phylogenetic succession of active ammonia oxidizers in protected vegetable soils - Weishou Shen; Dandan Li; Biyun Bian; Nan Gao; Zhongjun Jia; Xiangui Lin; Xinhua He; Wenhui Zhong (Applied Soil Ecology, 2026)

Prediction of energy consumption and carbon emission in Yunnan Province based on LEAP modeling - Zhengyuan Fan; Jie Yu; Taiwei Gu; Cui Qiao; Shaoyuan Li; Lin Ma; Wenhui Ma (Utilities Policy, 2026)

Tuning electron transfer and surface dual-sites for synergistic peroxymonosulfate activation toward efficient 2,4,6‑trichlorophenol degradation - Jingyi Wang; Yitong Liu; Wenhui Qiu; Lin Zhang; Kaige Li; Ran Wang; Bo Cao; Jianhua Qu; Ying Zhang (Process Safety and Environmental Protection, 2026)

The Hippo–Yki pathway governs growth and cell fate in the posterior silk gland of the silkworm - Yan Ma; Zhiyong Zhang; Wenhui Zeng; Zhou Fang; Xin Yu; Lin Cheng; Zehui Ma; Qipeng Zeng; Dena Jiang; Yiyun Tang; Jie Hu; Chen Zhao; et al. (Insect Biochemistry and Molecular Biology, 2026)

Correction: Stem Cell-Derived Exosomes Improve Neurological Dysfunction in a Rat Model of Moderate-to-Severe Cerebral Palsy - Tingting Peng; Huijuan Lin; Xiaoli Zeng; Yunlan Xie; Jie Luo; Lingjie Zhang; Shiya Huang; Zhiyi Ye; Xiaolin Guo; Wen Le; Mingtong Zhang; Wenhui Li; et al. (Stem Cell Reviews and Reports, 2026)

Mangrove species act as potential biofilters for legacy organochlorine pesticides: evidence from tissue-specific accumulation in the Zhangjiang Estuary - Nemin Luo; Ting Fang; Yingying Qian; Lei Wang; Wenhui Lin; Rongrong Song; Guoxin Li; Fengrun Wu; Xiaoqing Chen; Mingyuan Lin; Yan Lin (Marine Environmental Research, 2026)

Mechanistic insights into efficient phenol degradation mediated by anodic respiration in Acinetobacter sp. LA-1 - Binxin Liu; Jingyi Yu; Rongsheng Lin; Wendong Xian; Dan Luo; Li Chen; Jianxin Wang; Wenhui Wang; Qingqing Zhang; Peng Li (Journal of Hazardous Materials, 2026)

Non-progressive orogenesis of the Southern Tibetan Plateau - Xiaoyu Guo; Hengcheng Ying; Lin Chen; Rui Gao; Xiaofan Deng; Zhanwu Lu; Hongda Liang; Bo Xiang; Michael Murphy; Wenhui Li; Xiao Xu (Science Bulletin, 2026)

Long-term nitrogen and phosphorus amendments reshape arbuscular mycorrhizal regulation of hyphosphere microbial communities and functions in grassland soils - Dandan LI; Wenhui YAN; He YANG; Tao ZHANG; Timothy S. GEORGE; Stéphane DECLERCK; Lin ZHANG (Pedosphere, 2026)

Lysosomal dysfunction contributes to lead (Pb) and high-fat diet (HFD)-induced neuronal apoptosis: A link with cathepsin B - Yongke Yuan; Mengchen Liu; Mengdi Zhai; Meijia Wu; Wenhui Zhang; Yongjuan Xin; Yue Ba; Yu Zhang; Lin Han; Lihua Gao; Hui Huang (NeuroToxicology, 2026)

Variation characteristics and segment differences of urban heat exposure risk in continuous time series: A comprehensive synchronous comparison of daily and hourly scales - Junmao Zhang; Xia Yao; Meixia Lin; Tao Lin; Yuan Chen; Wenhui Li; Hongkai Geng; Yicheng Zheng; Zixu Jia; Hong Ye; Guoqin Zhang (Landscape and Urban Planning, 2026)

Stem Cell-Derived Exosomes Improve Neurological Dysfunction in a Rat Model of Moderate-to-Severe Cerebral Palsy - Tingting Peng; Huijuan Lin; Xiaoli Zeng; Yunlan Xie; Jie Luo; Lingjie Zhang; Shiya Huang; Zhiyi Ye; Xiaolin Guo; Wen Le; Mingtong Zhang; Wenhui Li; et al. (Stem Cell Reviews and Reports, 2026)

A synergistic strategy of high-entropy doping and transition metal vacancies for stable 4.5 V cycling of O3-type sodium-ion battery cathodes - Junwu Tian; Wenhui Chen; Mingbo Zheng; Yuqiao Jiang; Lin Lu; Yaohua Xiang; Yue Zhou; Xuanning Chen; Wei Wu; Zhenhui Liu; Zhenming Xu; Xiaogang Zhang; et al. (Chemical Engineering Journal, 2026)

Extracellular vesicles in pregnancy-related disorders: from mechanisms to clinical implications - Xiaojing He; Shiqi Liu; Yudi Wang; Hualongyue Du; Qiaoxi Lin; Wenhui Wang; Zihao Ou; Lei Zheng (Science China Life Sciences, 2026)

Controls of organic matter sources and hydrodynamic conditions on carbon and phosphorus contents in two karst reservoirs - Wenhui Wang; Yan Zeng; Jia Yu; Zhenzhen Ma; Yaoting Lu; Zuxue Jin; Lin Shi; Shuyun Xie; Jingfu Wang; Jingan Chen (Applied Geochemistry, 2026)

Design strategies based on hydrological performance of bioretention: experiments and modeling - Luwen Zhuang; Jianliang He; Jingmao Zhang; Gang Hu; Han Zhu; Wenhui Gan; Kairong Lin (Journal of Hydrology, 2026)

Optimization of gradient anisotropic voronoi porous structures based on machine learning - Wei Cao; Hanxuan Lin; Bin Liu; Pin Lu; Wenhui Shen; Jinwang Huang (Engineering Structures, 2026)

Atmospheric Submicron Aerosols Over the Tibetan Plateau: A Review - Lin Liang; Wenhui Zhao; Xiaomin Chen; Weiwei Hu; Pengfei Yu; Shan Huang (Current Pollution Reports, 2026)

Mechanism analysis and verification of silicon separation from diamond wire saw silicon slurry by sodium oleate flotation - Lin Zhu; Dandan Wu; Shicong Yang; Keqiang Xie; Kuixian Wei; Wenhui Ma (Process Safety and Environmental Protection, 2026)

Disentangling seasonal dynamics and transboundary transport of PAHs in a coastal monsoon city - Haolong Zhang; Zheng Zhang; Wenhui Lin; Guohui Lin; Cheng Luo; Ting Fang; Nemin Luo; Minggang Cai; Lei Wang; Bin Yan; Yan Lin (Atmospheric Research, 2026)

Vertical structure of the aerosols in the troposphere over the North China Plain: An analysis based on observations and simulations from 2007 to 2022 - Jiajun Xiong; Yi Wang; Minghui Tao; Wenhui Dong; Lin Zhou; Lunche Wang (Atmospheric Research, 2026)

CSN2 of COP9 signalosome underpins high temperature adaptation of the diatom Phaeodactylum tricornutum through regulating protein ubiquitination - Xin Li; Lu Zhou; Wenting Yang; Hong Wang; Xuehua Liu; Songcui Wu; Wenhui Gu; Lijun Wang; Xiujun Xie; Senjie Lin; Qiang Hu; Shan Gao; et al. (Algal Research, 2026)

Urban ecological risk assessment under water resources constraints: Framework development and application in Chinese cities - Zixu Jia; Tao Lin; Yuqin Liu; Hongkai Geng; Junmao Zhang; Yicheng Zheng; Xiangzhong Guo; Meixia Lin; Yuan Chen; Wenhui Liu; Jing Lin (Urban Climate, 2025)

Catechol-engineered manganese ferrite nanozyme with superior antioxidant activity promotes diabetic wound healing - Wenhui Wang; Leyu Zhang; Lin Yang; Xinsheng Li; Yan Xiao; Baocheng Chang; Yan Zhao; Ruxia Liu; Shao-Kai Sun (Chemical Engineering Journal, 2025)

A High Proportion of Milk Vetch-Rice Straw Co-Incorporation Enhances Soil C-N Cycling and Modulates Microbial Community Structure - Xiaoxue Ding; Luyuan Gao; Lin Chen; Wenhui Ma; Chunmei Wang; Fan Huang (Journal of Soil Science and Plant Nutrition, 2025)

Synergistic upcycling of silicon slag and waste graphite heaters for silicon carbide Synthesis: A sustainable approach to solid waste valorization - Yiyou Hu; Zhengjie Chen; Yonghang Zhang; Lin Wang; Panpan Hu; Wenhui Ma (Journal of Environmental Management, 2025)

Qualitative and quantitative detection of Zn2+ in food: design, synthesis and characterization of a near-infrared probe with large Stokes shift - Shizhen Wang; Xin Wang; Wenhui Xue; Yi Huo; Mengyu Chen; Cuibing Bai; Qixiang Song; Chenxu Liu; Lin Zhang; Changqing Qu; Hui Miao; Rui Qiao (Food Chemistry, 2025)

Investigation on the use of waste biomass as a carbonaceous reducing agent in industrial silicon smelting: Thermogravimetric analysis, cooperative behavior and reaction characteristic - Chenguang Han; Zhengjie Chen; Wenhui Ma; Lin Wang; Xiaowei Gan (Journal of Environmental Chemical Engineering, 2025)

Engineered biochar amended co-composting for greenhouse gas mitigation, nitrogen conservation, and eco-efficiency assessment - Yanyan Huang; Xu Yang; Jianhong Li; Hailong Wang; Hongzhu Yang; Tingting Yang; Dongming Zhang; Xianghui Zhang; Wenhui Lin; Caiwang Cheng; Paramsothy Jeyakumar; Ronghua Li; et al. (Journal of Environmental Chemical Engineering, 2025)

AIM2-PANoptosome-driven PANoptosis in hepatic lipid dysregulation induced by β-HCH and nanoplastics co-exposure - Qizhuan Lin; Helei Cai; Fan Yu; Changyong Gong; Yize Wu; Qiufang Wu; Feiqin Xie; Wenhui Xu; Shihua Chen; Xinxin Yao; Libo Jin; Renyi Peng (Apoptosis, 2025)

Assessments of Water Quality in Tibetan Plateau Require Focus on Heavy-Metal Indicators: Evidence from the Lhasa River - Bingdan Jiang; Yiming Tang; Yinjie Zhang; Wenhui Ju; Aijun Lin (Water, Air, & Soil Pollution, 2025)

Discovery of 7-azaindole-3-acrylamide inhibitors of inflammasomes/IL-1β for the treatment of inflammatory bowel disease - Yuyun Yan; Xiuxiu Zhang; Ruiwen Wu; Xiangting Liang; Yiming Luo; Jie Yang; Dan Wu; Geng Lin; Ping Sun; Zhongjin Yang; Wenhui Hu (Molecular Diversity, 2025)

The non-covalent and covalent interactions of whey proteins and saccharides: influencing factor and utilization in food - Yafei Zhang; Xiaoya Lin; Yiran Wang; Wenhui Ye; Yingying Lin; Yuning Zhang; Kai Zhang; Kaixuan Zhao; Huiyuan Guo (Critical Reviews in Food Science and Nutrition, 2025)

Developmental expression of α- and β- synuclein in the mouse retina - Wenhui Zhong; Zhongqun Chen; Shaoxuan Wang; Jun Cao; Xin Lin; Xiaoqian Lai; Bilin Rao; Jun Zhang (Brain Structure and Function, 2025)

Rapid screening of inorganic arsenic in groundwater on-site by a portable three-channel colorimeter - Xiaobao Tuo; Yanhua Duan; Guanting Lin; Tianci Jiang; Wenhui Liu; Fangyi Chen; Xianjun Xie; Yan Zheng (Journal of Environmental Sciences, 2025)

Photothermal cyclic self-healing coating with extended corrosion resistance utilizing Ag2S@Ti3C2 heterojunction - Wenhui Ji; Xiaohong Ji; Lin Cao; Qing Yu; Wei Wang (Journal of Environmental Chemical Engineering, 2025)

Structural resilience analysis of rural networks based on complex network theory - Xiaofei Tang; Yifan Cao; Wenhui Lin; Jinlong Chu; Jiulin Li (Frontiers of Earth Science, 2025)

A comparative metabolomics study of Panax ginseng infected by Fusarium oxysporum - Wenhui Lian; Chunhui Yu; Guijia Zhao; Xu Yang; Lin Feng; Jifeng Wang; Wei Liu; Yu Zhao (Journal of Plant Pathology, 2025)

Wide-area tip-like effect boosting electrocatalytic sulfion oxidation for energy-efficient hydrogen production in seawater electrolysis - Kecheng Tong; Wenhui Qiu; Shucong Zhang; Weiyue Zhao; Pingwei Wu; Fei Lin; Lei Chu; Huanlei Wang; Weiqian Tian; Minghua Huang (Chemical Engineering Journal, 2025)

Climate change enhances greening while human activities accelerate degradation in northern China's grasslands - Feifei Cao; Leizhen Liu; Yuping Rong; Nan Jiang; Lin Zhao; Qian Zhang; Zhitao Wu; Wenhui Zhao; Sheng Li (Science of The Total Environment, 2025)

Impact of mining activities on sediment resistance genes and microbial diversity along a receiving watershed - Guodong Chai; Yishan Lin; Kailong Li; Kai Chen; Wenhui Xu; Hui Wang; Jiake Li; Xiaosheng Jing; Haiyu Meng; Zhe Wang; Yuan Guo; Chunbo Jiang; et al. (Journal of Environmental Chemical Engineering, 2025)

Early-life exposure to outdoor temperature and the risk of childhood allergic diseases: A multicentre retrospective cohort study - Faming Wang; Lin Wang; Ying Jiang; Mengju Lan; Wenhui Yang; Zijing Liu; Chan Lu (Building and Environment, 2025)

Optimization study on circadian tunability and Rec. 2020 of RGB-LED-based displays considering the users with different ages - Qinzhen Lin; Ruoping Lian; Haoyang Liu; Wenhui Li; Junying Li; Yating Feng; Yi Lin; Suyao Liu; Weijie Liu; Kaiyu Yang; Yinxiao Yang; Yaling Chai; et al. (Energy and Buildings, 2024)

Vegetation greening mitigates the positive impacts of climate change on water availability in Northwest China - Zixu Jia; Tao Lin; Xiangzhong Guo; Yicheng Zheng; Hongkai Geng; Junmao Zhang; Yuan Chen; Wenhui Liu; Meixia Lin (Journal of Hydrology, 2024)

Emission characteristics and process distributions of multiple brominated persistent organic pollutants during co-disposal of hexabromocyclododecane-containing waste in a municipal solid waste incinerator - Wenhui Xie; Bingcheng Lin; Yaqi Peng; Bei Chen; Yuchun Wang; Yuxuan Ying; Shengyong Lu; Tong Chen (Journal of Environmental Management, 2024)

Sugarcane ScOPR1 gene enhances plant disease resistance through the modulation of hormonal signaling pathways - Wenhui Zou; Tingting Sun; Yao Chen; Dongjiao Wang; Chuihuai You; Shoujian Zang; Peixia Lin; Qibin Wu; Yachun Su; Youxiong Que (Plant Cell Reports, 2024)

Cell-specific localization of β-synuclein in the mouse retina - Wenhui Zhong; Qingwen Yang; Fenglan Wang; Xin Lin; Zhongqun Chen; Jing Xue; Wenna Zhao; Xiaoqing Liu; Bilin Rao; Jun Zhang (Brain Structure and Function, 2024)

Buried interface modulation by rubidium dihydrogen phosphate towards highly effective perovskite solar cells - Puzhao Yang; Jihuai Wu; Wenhui Lin; Xiaoyuan Jiang; Ying Wang; Weihai Sun; Zhang Lan; Jianming Lin (Chemical Engineering Journal, 2024)

Exploring the differences between express and ride-pooling: A dual perspective on user perception and functional positioning in urban traffic system - Ying Lu; Shuyue Yao; Hongzhi Lin; Jianqiang Cui; Wenhui Yu (Travel Behaviour and Society, 2024)

Comparison of life cycle assessment between hydrogen production from silicon waste and alkaline water electrolysis - Shengqiang Yang; Dan Mao; Zhiqiang Yu; Wenhui Ma; Lin Ma; Xiufeng Li; Fengshuo Xi (Science of The Total Environment, 2024)

PbWRKY18 promotes resistance against black spot disease by activation of the chalcone synthase gene PbCHS3 in pear - Xin Wang; Qinghai Qiao; Keke Zhao; Wenhui Zhai; Feng Zhang; Huizhen Dong; Likun Lin; Caihua Xing; Zhiyuan Su; Zhijian Pan; Shaoling Zhang; Xiaosan Huang (Plant Science, 2024)

Trifluoperazine activates AMPK / mTOR / ULK1 signaling pathway to induce mitophagy in osteosarcoma cells - Wenhui Shen; Xiangchen Zeng; Xianhui Zeng; Baoshan Hu; Chong Ren; Zhiming Lin; Long Zhang; Gang Rui; Miersalijiang Yasen; Xiaohui Chen (Chemico-Biological Interactions, 2024)

Multi-source exposure and health risks of phthalates among university students in Northeastern China - Huicheng Zhu; Na Zheng; Changcheng Chen; Ning Li; Qirui An; Wenhui Zhang; Qiuyan Lin; Zhifei Xiu; Siyu Sun; Xiaoqian Li; Yunyang Li; Sujing Wang (Science of The Total Environment, 2024)

Intramolecular carbon isotopic rollover in propane from natural gas reservoirs of the Santanghu Basin: Insights into chemical structure of kerogen - Peng Liu; Xiaofeng Wang; Changjie Liu; Ying Lin; Ruiliang Guo; Wenhui Liu (Organic Geochemistry, 2024)

Abscisic acid promotes selenium absorption, metabolism and toxicity via stress-related phytohormones regulation in Cyphomandra betacea Sendt. (Solanum betaceum Cav.) - Xun Wang; Wen Lu; Ziming Zhao; Wenhui Hao; Ruimin Du; Zhiyu Li; Zhihui Wang; Xiulan Lv; Jin Wang; Dong Liang; Hui Xia; Yi Tang; et al. (Journal of Hazardous Materials, 2024)

Overview of life cycle assessment of recycling end-of-life photovoltaic panels: A case study of crystalline silicon photovoltaic panels - Dan Mao; Shengqiang Yang; Lin Ma; Wenhui Ma; Zhiqiang Yu; Fengshuo Xi; Jie Yu (Journal of Cleaner Production, 2024)

Blue polyimides for high-performance solution-processable organic light-emitting diodes - Wenhui Wang; Kaijin Chen; Chuying Li; Faxu Lin; Yuxuan Li; Yubo Long; Juan Zhao; Siwei Liu; Zhenguo Chi; Jiarui Xu; Yi Zhang; Yuguang Ma (Chemical Engineering Journal, 2024)

Depth profiles of microplastics in sediments from inland water to coast and their influential factors - Bing Yuan; Wenhui Gan; Jian Sun; Binliang Lin; Zhihe Chen (Science of The Total Environment, 2023)

One-step desilication-recrystallization towards enhanced diffusion for Ni/ZSM-5-catalyzed n-hexane hydrogenative isomerization - Ye Song; Bo Peng; Ruoyu Wang; Lei Han; Wenhui Zhao; Lei Wang; Haitao Song; Wei Lin (Chemical Engineering Journal, 2023)

Coupling the digital twin technology and life cycle assessment: Carbon dioxide emissions from polysilicon production - Shengqiang Yang; Zhiqiang Yu; Wenhui Ma; Lin Ma; Chaochun Li; Ling Fu; Ming Li; Zewen Zhao; Yuchen Yang (Sustainable Production and Consumption, 2023)

Metabolomic profiling of Panax ginseng in response to Fusarium solani infection - Guijia Zhao; Shuyang Xing; Yang Wang; Xu Yang; Ru Sun; Lin Feng; Jifeng Wang; Tianxia Sun; Wenhui Lian; Yu Zhao (Physiological and Molecular Plant Pathology, 2023)

Association between prenatal exposure to trace elements mixture and visual acuity in infants: A prospective birth cohort study - Zijin Wang; Yuanyan Dou; Wenhui Guo; Yuan Lin; Yangqian Jiang; Tao Jiang; Rui Qin; Hong Lv; Qun Lu; Guangfu Jin; Hongxia Ma; Zhibin Hu; et al. (Chemosphere, 2023)

Distribution and synaptic organization of substance P-like immunoreactive neurons in the mouse retina - Fenglan Wang; Wenhui Zhong; Qingwen Yang; Wenna Zhao; Xiaoqing Liu; Bilin Rao; Xin Lin; Jun Zhang (Brain Structure and Function, 2023)

A sustainable layered nanofiber/sheet aerogels enabling repeated life cycles for effective oil/water separation - Ting Dong; Huabiao Ye; Wenhui Wang; Yuanming Zhang; Guangting Han; Fudi Peng; Ching-Wen Lou; Shan Chi; Yanming Liu; Cui Liu; Jia-Horng Lin (Journal of Hazardous Materials, 2023)

Correlation between tumor cell migration and formaldehyde levels revealed by fluorescence imaging - Wei Quan; Yanxia Li; Wenhui Song; Zihong Li; Qian Zhang; Weiying Lin (Chemical Engineering Journal, 2023)

Characteristics of Cloud Water Resource and Precipitation Efficiency of Hydrometeors over Northwest China - Zhanyu Yao; Lin An; Pei Zhang; Liangshu Gao; Shuo Jia; Weijian Wang; Wenhui Zhao (Journal of Meteorological Research, 2023)

Identification and hepatoprotective activity of total glycosides of paeony with high content of paeoniflorin extracted from Paeonia lactiflora Pall - Lin Peng; Zhe Ma; Wenhui Chu; Peisi Jiang; Yongqian Fu; Pan Wang (Food and Chemical Toxicology, 2023)

Dynamic changes in cell wall-degrading enzymes and physio-biochemistry of ginseng in response to fusarium oxysporum infection - Lin Feng; Guijia Zhao; Ru Sun; Jifeng Wang; Tianxia Sun; Shuyang Xing; Wenhui Lian; Yu Zhao (European Journal of Plant Pathology, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Large-flake graphene-modified biochar for the removal of bisphenol S from water: rapid oxygen escape mechanism for synthesis and improved adsorption performance - Yurong Gao; Zheng Fang; Wenhui Lin; Hanbo Chen; Amit Bhatnagar; Jianhong Li; Yanhai Xie; Yanping Bao; Junfeng Chen; Hongting Zhao; Jun Meng; Wenfu Chen; et al. (Environmental Pollution, 2023)

Moisture effects on the active prokaryotic communities in a saline soil unraveled by 18O-informed metagenomics - Yeliang Dai; Yanshuo Pan; Yue Sun; Jun Zeng; Guangming Liu; Wenhui Zhong; Xuanzhen Li; Yucheng Wu; Xiangui Lin (Journal of Soils and Sediments, 2021)

Photosensitive hydrogels: from structure, mechanisms, design to bioapplications - Wenhui Ji; Qiong Wu; Xisi Han; Wei Zhang; Wei Wei; Liang Chen; Lin Li; Wei Huang (Science China Life Sciences, 2020)

GPI7‐mediated glycosylphosphatidylinositol anchoring regulates appressorial penetration and immune evasion during infection of Magnaporthe oryzae - Caiyun Liu; Junjie Xing; Xuan Cai; Ahmed Hendy; Wenhui He; Jun Yang; Junbing Huang; You‐Liang Peng; Lauren Ryder; Xiao‐Lin Chen (Environmental Microbiology, 2020)
Summary Glycosylphosphatidylinositol (GPI) anchoring plays key roles in many biological processes by targeting proteins to the cell wall; however, its roles are largely unknown in plant pathogenic fungi. Here, we reveal the roles of the GPI anchoring in Magnaporthe oryzae during plant infection. The GPI‐anchored proteins were found to highly accumulate in appressoria and invasive hyphae. Disruption of GPI7 , a GPI anchor‐pathway gene, led to a significant reduction in virulence. The Δ gpi7 mutant showed significant defects in penetration and invasive growth. This mutant also displayed defects of the cell wall architecture, suggesting GPI7 is required for cell wall biogenesis. Removal of GPI‐anchored proteins in the wild‐type strain by hydrofluoric acid (HF) pyridine treatment exposed both the chitin and β‐1,3‐glucans to the host immune system. Exposure of the chitin and β‐1,3‐glucans was also observed in the Δ gpi7 mutant, indicating GPI‐anchored proteins are required for immune evasion. The GPI anchoring can regulate subcellular localization of the Gel proteins in the cell wall for appressorial penetration and abundance of which for invasive growth. Our results indicate the GPI anchoring facilitates the penetration of M. oryzae into host cells by affecting the cell wall integrity and the evasion of host immune recognition.

Late Early-Cretaceous Magma Mixing in the Langqi Island, Fujian Province, China: Evidences from Petrology, Geochemistry and Zircon Geochronology - Liangliang Huang; Liyuan Wang; Hong-Rui Fan; Musen Lin; Wenhui Zhang (Journal of Earth Science, 2020)

Effects of simulated nitrogen deposition on Phyllostachys edulis (Carr.) seedlings under different watering conditions: is seedling drought tolerance related to nitrogen metabolism? - Wenhui Shi; Lin Lin; Shanlu Shao; Anguo He; Yeqing Ying (Plant and Soil, 2020)

Identification and molecular characterization of Serratia marcescens phages vB_SmaA_2050H1 and vB_SmaM_2050HW - Changyu Tian; Jiangtao Zhao; Zheng Zhang; Xiao Chen; Xiao Wei; Huan Li; Weishi Lin; Yuehua Ke; Lingfei Hu; Aimin Jiang; Ruo Feng; Wenhui Yang; et al. (Archives of Virology, 2019)

Declining hailstorm frequency in China during 1961–2015 and its potential influential factors - Wenhui Zhao; Jianping Guo; Zhanyu Yao; Yuxing Yun; Shuo Jia; Weijian Wang; Pei Zhang; Hui Xu; Huan Liu; Liangshu Gao; Yanluan Lin; Mingxin Li; et al. (International Journal of Climatology, 2018)
Based on 55 years (from 1961 to 2015) of ground‐based hailstorm and atmospheric sounding observations, the climatological characteristics of hailstorms in China, along with potential influencing factors, were analysed. We found that hailstorms exhibit large spatial and temporal variability, with the peak occurring in spring in south China, and in summer in north China. The Tibetan Plateau (TTP) is a region with high hailstorm frequency. Overall, the frequency of hailstorms has decreased over the 55 years, although there was an increase from 1961 to 1985. In terms of diurnal variability, while hailstorm frequency peaks in the afternoon in most of China, it peaks during the night or early morning in southwest China. The magnitude of the peak increased during the 1960s and 1970s, and then decreased afterwards. Hailstorms are negatively correlated with daily mean temperature but are positively correlated with diurnal temperature range, convective available potential energy (CAPE) and totals–totals index. The increase of hailstorms during the period from 1961 to 1985 is mainly correlated with the increase in CAPE over the TTP region, while the decrease of hailstorms afterwards is correlated with all four convective parameters. The finding has significant implications for the potential impact of increasing greenhouse gases on climatological changes in hailstorm.

Development of a Xanthene-Based Red-Emissive Fluorescent Probe for Visualizing H2O2 in Living Cells, Tissues and Animals - Nan Zhang; Baoli Dong; Xiuqi Kong; Chao Wang; Wenhui Song; Weiying Lin (Journal of Fluorescence, 2018)

Sorting nexin (MoVps17) is required for fungal development and plant infection by regulating endosome dynamics in the rice blast fungus - Huawei Zheng; Zhongkun Guo; Yang Xi; Mingyue Yuan; Yahong Lin; Congxian Wu; Yakubu Saddeeq Abubakar; Xianying Dou; Guangpu Li; Zonghua Wang; Wenhui Zheng; Jie Zhou (Environmental Microbiology, 2017)
Summary Vps17 is a sorting nexin (SNX) and a component of the retromer, a protein complex mediating retrograde vesicle transport between endosomes and the trans‐Golgi network. However, its role in the development and pathogenicity of filamentous fungi such as the rice blast fungus ( Magnaporthe oryzae ) remains unclear. We investigate the functional relationship between the SNX and the cargo‐selective complex (CSC) of the fungal retromer by genetic analysis, live cell imaging and immunological assay. Our data show that the MoVps17 null mutation causes defects in growth, development and pathogenicity in M. oryzae . MoVps17 is localized to endosomes depending on the activity of phosphatidylinositol 3‐kinase (PI3K), a key enzyme for fungal development and infection. Both PX and BAR domains of MoVps17 are essential for its endosomal localization and function. Furthermore, our yeast two‐hybrid assays show that MoVps17 and MoVps5 can interact. Lastly, live cell imaging suggests that MoVps17 can regulate early endosome fusion and budding as well as endocytosis. Taken together, our results suggest that MoVps17 specifically functions as a retromer component with CSC and also plays a distinct role in the regulation of endosome dynamics during fungal development and plant infection.

The climatic impacts of land use and land cover change compared among countries - Jiyuan Liu; Quanqin Shao; Xiaodong Yan; Jiangwen Fan; Jinyan Zhan; Xiangzheng Deng; Wenhui Kuang; Lin Huang (Journal of Geographical Sciences, 2016)

Association of Enterovirus 71 encephalitis with the interleukin-8 gene region in Chinese children - Jian Li; Aiwei Lin; Chengwen Yu; Zhaofang Zhang; Daoyan Xu; Wei Hu; Liyan Liu; Shaoning Wang; Xiuzhen Nie; Wenhui Sun; Zhongtao Gai; Zongbo Chen (Infectious Diseases, 2015)

Comparison and development of EST–SSRs from two 454 sequencing libraries of Gossypium barbadense - Hantao Wang; Ximei Li; Wenhui Gao; Xin Jin; Xianlong Zhang; Zhongxu Lin (Euphytica, 2014)

Dendrochronology-based stand growth estimation of Larix olgensis forest in relation with climate on the eastern slope of Changbai Mountain, NE China - Bo Lin; Qianqian Xu; Wenhui Liu; Guochun Zhang; Qiongyao Xu; Qijing Liu (Frontiers of Earth Science, 2013)

Perfluorinated Compounds in Surface Water and Organisms from Baiyangdian Lake in North China: Source Profiles, Bioaccumulation and Potential Risk - Zhen Zhou; Yali Shi; Wenhui Li; Lin Xu; Yaqi Cai (Bulletin of Environmental Contamination and Toxicology, 2012)

Analysis of forest damage caused by the snow and ice chaos along a transect across southern China in spring 2008 - Quanqin Shao; Lin Huang; Jiyuan Liu; Wenhui Kuang; Jia Li (Journal of Geographical Sciences, 2011)

The effects of restoration techniques on protozoan communities in mandarin fish culture ponds, based on an artificial substrate - Jianrong Huang; Wenhui Lin; Cunbing Shi; Shuqin Wu; Runlin Xu (Aquaculture International, 2010)

The effects of mineral fertilizer and organic manure on soil microbial community and diversity - Wenhui Zhong; Ting Gu; Wei Wang; Bin Zhang; Xiangui Lin; Qianru Huang; Weishou Shen (Plant and Soil, 2010)

The effects of mineral fertilizer and organic manure on soil microbial community and diversity - Wenhui Zhong; Ting Gu; Wei Wang; Bin Zhang; Xiangui Lin; Qianru Huang; Weishou Shen (Plant and Soil, 2010)